Composite materials for the structural strengthening of reinforced masonry shells - Barros, Joaquim A. O. (2007)
Since the 1950s, the Uruguayan engineer Eladio Dieste designed curved lightweight masonry shells of impressive span width, complex shape and high attractiveness. This structural system is composed of a top mortar cover, a layer of clay bricks, mortar joints, and steel reinforcement. For the permanent loads, this structural system has been working satisfactory, in spite of rebar corrosion being detected in some shells. However, if submitted to an earthquake of considerable magnitude, damage can be significant, and its rupture can even occur. In the present paper, an effective strengthening technique, using carbon fibre reinforced polymer (CFRP) materials, was developed to significantly increase the ultimate load of damaged reinforced masonry shell structures. This strengthening system is composed by strips of wet lay-up CFRP sheet and prefabricated CFRP laminates. The sheet strips are bonded, with epoxy resin, to the top cracked concrete surface of the shell to increase its flexural resistance for the negative bending moments, while laminates are fixed, with epoxy adhesive, to the bottom of the reinforced concrete joints to increase the shell flexural resistance for the positive bending moments. This strengthening system was applied to a damaged shell, having resulted a significant increase in the service load and an increase of about 76% in the ultimate load. A monitoring system was installed to evaluate the applied force, the deflection in critical sections and the strains in the composite materials and in the steel reinforcement. The experimental research is described and the main results are presented and discussed.